Nonunique Coincidence Point Results via Admissible Mappings - Erdal Karapınar; Chi-Ming Chen; Andreea Fulga (Journal of Function Spaces, 2021)
This paper is aimed at presenting some coincidence point results using admissible mapping in the framework of the partial b-metric spaces. Observed results of the article cover a number of existing works on the topic of “investigation of nonunique fixed points.” We express an example to indicate the validity of the observed outcomes.